Rapamycin Modulates the Proinflammatory Memory-Like Response of Microglia Induced by BAFF - Wang, Jianing; Yang, Chunshu; Hou, Xiaoyu; Xu, Jingyi; Yun, Yang; Qin, Ling; Yang, Pingting (Frontiers in Immunology, 2021)
Background Recently trained immunity of microglia provided an opportunity to study the chronic effect of microglial activation and its metabolic rewiring in neuroimmunological diseases. Since elevated levels of B cell-activating factor (BAFF) have been proved to be associated with some chronic neuroimmunological disorders. Here, we used the trained innate immunity model to analyze the effect of BAFF, a vital regulator of the adaptive immune system, on long-term microglial activation and metabolic reprogramming in vitro and in vivo. Methods and results In vitro, BV2 cells and mouse primary microglial cells were incubated with BAFF for 24 h (BAFF priming). After 5 days of resting, microglia were restimulated with LPS (LPS restimulation) or BAFF (BAFF restimulation). BAFF priming induced a pro-inflammatory trained immunity-phenotype of both BV2 cells and primary microglial cells, which was indicated by morphological change, secretion of pro-inflammatory cytokine and chemokine upon LPS restimulation or BAFF restimulation. The production of lactate and NAD+/NADH ratio were elevated 5 days after BAFF priming. The activation of the Akt/mTOR/HIF-1α pathway was induced by BAFF priming and lasted for 5 days. Pretreating the BV2 cells or mouse primary microglial cells with rapamycin blocked mTOR/HIF-1α activation and cellular metabolic reprogramming induced by BAFF training. Consistently, rapamycin efficiently suppressed the trained immunity-like responses of microglia triggered by BAFF. In vivo, adult male mice were treated with BAFF by intracerebroventricular injection for priming and 7 days later with BAFF for restimulation. BAFF training activated microglia in the cortex and hippocampus. The production of proinflammatory cytokines and chemokines was elevated after BAFF training. Conclusion Our current data, for the first time, demonstrate that BAFF priming induces a proinflammatory memory-like response of microglia not only to LPS but also to BAFF itself. Rapamycin inhibits microglial priming triggered by BAFF through targeting the mTOR/HIF-1α signaling pathway. Our data reveal a novel role of BAFF in trained immunity and that rapamycin may be a potential therapeutic target of neuroimmunological diseases.